Performance Management 2e - Bagchi, Soumendra Narain (Andover, Melbourne Cengage Learning, 2013)
"Performance Management is a guide to the fundamental principles of training, learning and development. Tailored to the needs of HR practitioners it offers a complete overview of the field strongly aligned to organizational and HR strategies and objectives. Using a combination of practical tools, assessments, scenarios and case studies from best practice it will build your knowledge of the area including motivation, key competencies, types of assessment and performance review and dealing with underperformance. Aligning performance management with strategic objectives it will equip you with the skills you need to plan, implement and assess relations in any type of organization"-
Include Index
Keywords: Performance--Management -- Personnel management